Nutrition for Gestational Diabetes (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Gestational diabetes mellitus (GDM) is one of the most common adverse medical conditions that occurs during pregnancy, and its prevalence is rising as part of a diabetes pandemic. Nutrition plays a key role in GDM, whether (1) as part of an ‘unhealthy’ diet, which contributes to its cause, or (2) as part of changes in dietary intake, which act as the frontline treatment for GDM (sometimes supplemented with exercise and pharmacological intervention). Dietary changes, therefore, can alter the risk of developing GDM in the first place, and once GDM has emerged during pregnancy, dietary changes can mitigate the risk of developing GDM-related complications, such as macrosomia, respiratory distress, hypoglycemia and jaundice in the neonate, pre eclampsia, increased need for caesarean section and placental abruption in the mother. In this Special Issue, we aim to highlight the role of nutrition in the aetiology of GDM, whether directly or indirectly through weight gain and obesity, and in its role as a GDM treatment to lower hyperglycemia and the risk of the aforementioned complications.